P2_6_Playing_the_saxophone:_growling_v1 - Francis, William; Harrison, James; Carr, Edward (Physics Special Topics, 2009)
A technique in Jazz and blues saxophone is to hum or sing a note into the saxophone. The technique is called growling due to the sound produced sounding much like a growl. It is thought to produce a more gritty and emotional sound to the saxophone. This paper investigates the effect upon the sound frequcney produced in this technique.